Combination drug screen identifies synergistic drug interaction of BCL-XL and class I histone deacetylase inhibitors in MYC-amplified medulloblastoma cells - Zeuner, Simon; Vollmer, Johanna; Sigaud, Romain; Oppermann, Sina; Peterziel, Heike; ElHarouni, Dina; Oehme, Ina; Witt, Olaf; Milde, Till; Ecker, Jonas (Journal of neuro-oncology, 2024)
Purpose: Patients with MYC-amplified Group 3 medulloblastoma (MB) (subtype II) show poor progression-free survival rates. Class I histone deacetylase inhibitors (HDACi) are highly effective for the treatment of MYC-amplified MB in vitro and in vivo. Drug combination regimens including class I HDACi may represent an urgently needed novel treatment approach for this high risk disease. Methods: A medium-throughput in vitro combination drug screen was performed in three MYC-amplified and one non-MYC-amplified MB cell line testing 75 clinically relevant drugs alone and in combination with entinostat. The drug sensitivity score (DSS) was calculated based on metabolic inhibition quantified by CellTiter-Glo. The six top synergistic combination hits were evaluated in a 5 × 5 combination matrix and a seven-ray design. Synergy was validated and characterized by cell counts, caspase-3-like-activity and poly-(ADP-ribose)-polymerase-(PARP)-cleavage. On-target activity of drugs was validated by immunoprecipitation and western blot. BCL-XL dependency of the observed effect was explored with siRNA mediated knockdown of BCL2L1, and selective inhibition with targeted compounds (A-1331852, A-1155463). Results: 20/75 drugs effectively reduced metabolic activity in combination with entinostat in all three MYC-amplified cell lines (DSS ≥ 10). The combination entinostat and navitoclax showed the strongest synergistic interaction across all MYC-amplified cell lines. siRNA mediated knockdown of BCL2L1, as well as targeted inhibition with selective inhibitors showed BCL-XL dependency of the observed effect. Increased cell death was associated with increased caspase-3-like-activity. Conclusion: Our study identifies the combination of class I HDACi and BCL-XL inhibitors as a potential new approach for the treatment of MYC-amplified MB cells.